An emotion-based model of criminal investigators' competences in Polícia de Segurança Pública - Moura, Rui Filipe Resende Melo Coelho de (2018)
Competence is a core concept in HRM as it offers the possibility of being the strategic reference around which all HR practices are articulated. Competence models and profiling have been developing by integrating extant literature but are yet to fully grasp the role emotions play in daily organizational life. The present research is set to explore emotion-based competence modelling by focusing on an emotional demanding profession: that of criminal investigator, linking with recruitment and selection as well as initial training. After reviewing the institutional context in which criminal investigators work (PSP), the study starts by exploring police recruitment and selection, and initial training practices in European police forces, focusing both on officials and officers. Findings showed divergences both between police forces and careers thus showing no emergent pattern on these issues. More importantly, no emotion-driven practices was reported. The research evolved to explore how emotions could be mapped under the performance agenda conditioning the entire building of competence model as proposed by Bartram and Roe (2005). With a sample of 703 questionnaires filled in by criminal investigators we collected data on emotional commands, personality, abilities, knowledge, skills, attitudes and values to test a sequential set of relations between these constructs. Findings from SEM analysis show streams of associations linking emotional commands up to specific competences, moderated at certain level by values. The resulting syncretic model addressed both competences and emotions (at the lowest layer), following a modelling methodology in sequenced layers (interfaces) which rendered it a different composition and relation between layers. Findings suggest that it is possible to structure a competence model for criminal investigators with emotions considered at the ground layer as the emotional foundations of human personality (Davis & Panksepp, 2011) expressed as the Emotion Command Systems.